E-Trust and E-Service Quality on E-Loyalty: Role of E-Satisfaction and Customer Privacy - ., Rohwiyati; Haryono , Tulus; Setiawan , Ahmad Ikhwan; Wahyudi , Lilik; Amperawati , Endang Dwi; Pradianto, Mi’raj Akbar (Journal of Ecohumanism, 2024)
Main objective: investigate effect ET and ESQ on ELOY through ESAT and effect ESAT on ELOY moderated privacy. Background Problem: E-Trust, E-service quality and weak privacy of Shopee customers still need to be improved because it will affect the decline in E-loyalty. Novelty: the importance of strengthening the privacy system that is difficult to hack in the Shopee application so that customer privacy is truly protected from cyber hacking. Research Methods: samples of 265 Shopee customers in Central Java Indonesia, PLS-SEM used for data analyzing. Results: ET and ESQ have a positive link to ESAT; the effect of ET, ESQ and ESAT on ELOY is also positive. ET and ESQ affect ELOY through ESAT; the effect of ESAT on ELOY can be moderated by privacy. Conclusion: E-Satisfaction is effective as an intermediary variable for E-Trust and E-Servqual in influencing E-Loyalty of Shopee customers and privacy is effective as a moderating variable in the influence of E-Satisfaction on E-Loyalty.